Finite Element Modelling and Updating of Motorcycle Structure with Suitable Length of Connecting Element - M. S. M., Sani; K. M., Jelani; N. A. Z., Abdullah; M. N., Abdul Rani; M. A., Yunus (Society Vibration Acoustics Malaysia, 2023)
This paper attempts to present an appropriate way to model welded joints in a motorcycle structure using the finite element method. Joint modelling strategy was implemented in this study since the joint itself has a significant influence as local effect on dynamic behavior of a structure. The objective of the paper is to investigate the suitable length of connecting element for joints of the structure. The length of the gaps of the parts is a 3mm, 10mm and 15mm was created in 3D model of structure for this joint modelling purpose. The element connectors that available in the FEA software were utilized to model the welded at assembled parts on test structure in this study. Two locations were used on the FE model for modelling of welded joints such as CBAR element connector used to replicate spot weld joint. Ahead of the updating process, sensitivity analysis is made to select the most sensitive parameter for updating purpose. Optimization algorithm in MSC Nastran is used in FE model updating process. The results show that employing a gap connecting element as an updating parameter (3mm) offers greater convergence than using significant parameters. This paper concluded that suitable length of connecting element for joint structure with CBAR element connector is attainable to replicate the real welded motorcycle structure since it has the lowest discrepancy in correlation analysis.